Thom's official directory of the United Kingdom of Great Britain and Ireland for the year 1904 (pages 417-605) - http://id.worldcat.org/fast/2012713 (Alex. Thom & Co. (Limited), 1904)
"Comprising British, foreign, and colonial directories. Parliamentary directory, Peerage, baronetage, and knightage directory. Naval and military directory. Statistics of Great Britain and Ireland. Government offices directory. University, scientific, and medical directory., Law directory. Ecclesiastical directory. Banking directory. Postal directory. County and borough directory. Lieutenancy and magistracy of Ireland. Post office Dublin city and county directory, with a new coloured map of Dublin and its environs."